Compact low-cost substrate integrated waveguide fed antenna for 122 GHz radar applications. Issue 4 (20th February 2019) - Frank, Martin; Lurz, Fabian; Weigel, Robert; Koelpin, Alexander
Abstract: This paper describes the design and characterization of a compact substrate integrated waveguide (SIW) fed antenna for the 122 GHz industrial, scientific, and medical band. The use of a single RO4350B substrate layer and the SIW feeding ensure a low-cost fabrication. Two versions of the antenna are presented differing in antenna gain and size. For measurement purpose, a transition from rectangular waveguide to SIW is introduced. Measurements of the radiation pattern have been performed and show good agreement with the numerical results for both antennas and an antenna gain up to 7.14 dBi.